Detecting small-scale geological structures using diffraction attributes - Wang Juhe; Chen Xiuping; Shu Mengcheng; Cheng Sen (E3S Web of Conferences, 2022)
We developed a method that uses diffracted wave data to address the issue of precisely characterizing small geological structures in a reservoir and demonstrated its effectiveness using model calculations. The method was implemented to characterize a fractured reservoir and igneous rock intruded in a carbonate reservoir. Two diffraction attributes were analyzed to precisely characterize the fine, small-scale geological structures therein. Principal component analysis was performed to extract diffraction data from seismic wave fields, and the reflection and diffraction wave fields were separated based on the kinematics and dynamics of the diffracted waves. The resulting diffracted wave fields provided an excellent basis upon which to assess the distribution of small geological structures in the study area. This proved, experimentally, that our diffraction-based method has the potential to characterize the distribution of small geological structures precisely and holistically.